`4714/6 =(4710+4)/6 =4710/6 +4/6 =(785*6)/6 +(2*2)/(2*3) =`

`=785+2/3 (=785 2/3)=785+0.(6) =785.(6)`

First we have decomposed the number 4714 into a sum of two numbers, first number being the highest possible multiple of 6 that is smaller than 4714 and a second number that completes the addition. Thus the first number divided by 6 was an integer. Next we factorized both the second number and the divider 6, and simplified the common factors. Hence we obtained the result of the division of 4714 to 6 as being `785 2/3` , which further can be written as `785.6666...=785.(6)`

**Answer:** **4714 divided by 6** `=785 2/3 =785.(6)`